Ebstein’s Anomaly with Paraplegia in The Two Lower Extremities: A Surprising Diagnosis in Adult Woman—A Rare Case Report - Ryan Ardiansyah; Rinjani, Lalu Galih Pratama (Universitas Airlangga, 2025)
Background: Ebstein's anomaly (EA) is a rare condition of congenital heart disease and a malformation of the tricuspid valve with myopathy of the right ventricle, Ebstein anomaly is estimated to occur at a rate of 0.17 to 0.72 per 10,000 live births and has no correlation with gender or race. Case Summary: We report the rare case in adult women patient from East Lombok West Nusa Tenggara Indonesia, is diagnosed with Ebstein’s Anomaly. The patient came to the emergency department presented with symptoms of paraplegia with palpitation. She had paraplegia until twelve years a go and diagnosis is confirmed by echocardiography with result of sistolic function of LV is normal EF 68%, but diastolic function of LV difficult to evaluate and sistolic function of RV difficult to evaluate, additionally, moderate mitral regurgitation, Thrombus in Right Atrium diameters of 2.4x4.8 cm, Tricuspid valve difficult to evaluate, and high probability of pulmonary hypertension, electrocardiogram (ECG) revealed Atrial fibrilation with rapid ventricular respons and Chest radiography showed a globe-shaped heart, with normal vascularity and a cardiothoracic ratio of above 0.5 is considered abnormal and may indicate cardiomegaly. The patient received medical treatment, which provided significant relief. Conclusion: From this case we wished to point out to show that early screening of congenital heart disease is important to life saving, further research in this case is needed to know that the possible paraplegia due to venous thrombosis of ebstein's anomaly. - Highlights: This rare case highlights an unusual presentation of Ebstein’s anomaly associated with paraplegia, possibly related to venous thrombosis. Early screening and echocardiographic evaluation of congenital heart disease remain essential for timely diagnosis and life-saving management